The Glass Ceiling for Women Managers: Antecedents and Consequences for Work-Family Interface and Well-Being at Work - Babic, Audrey; Hansez, Isabelle (Frontiers in Psychology, 2021)
Despite significant promotion of diversity in companies, as well as legislation for equal opportunities for women and men, it must be noted that women still remain largely in the minority in decision-making positions. This observation reflects the phenomenon of the glass ceiling that constitutes vertical discrimination within companies against women. Although the glass ceiling has generated research interest, some authors have pointed out that theoretical models have made little attempt to develop an understanding of this phenomenon and its implications. Therefore, our study aims to fill this gap and to better understand the phenomenon of the glass ceiling by considering both its antecedents and its possible consequences. More precisely, we extend the model developed by Elacqua et al. (2009), proposing a more comprehensive model including organizational gender culture as a third factor (in addition to situational and interpersonal issues) in the emergence of the glass ceiling through the perception of differential treatment. We also investigated the glass ceiling’s consequences for organizational attitudes and well-being at work by considering work-to-family conflict (WFC) as a possible mediator. We surveyed 320 women in managerial positions in a Belgian organization. Our study highlights the importance of all three factors in the emergence of the perception of differential treatment and, ultimately, the perception that a glass ceiling exists. Moreover, our results show that WFC fully mediates the effects of the glass ceiling on job strain and job engagement, and partially mediates the effects of the glass ceiling on job satisfaction and intention to quit.